Comparative analysis on grain quality and yield of different panicle weight indica-japonica hybrid rice (Oryza sativa L.) cultivars - Jin-long BIAN; Gao-lei REN; Chao HAN; Fang-fu XU; Shi QIU; Jia-hua TANG; Hong-cheng ZHANG; Hai-yan WEI; Hui GAO (Journal of Integrative Agriculture, 2020)
Indica-japonica hybrid rice (Oryza sativa L.) cultivars showed high yield potential and poor tasting quality when compared with common japonica rice cultivars. Large panicle is a prominent factor of high yield for indica-japonica hybrid rice cultivars, and the panicle weight varies greatly among different indica-japonica hybrid rice cultivars. It is important to research on yield and grain quality of different panicle weight indica-japonica hybrid rice cultivars. In this study, two different panicle types indica-japonica hybrid cultivars were used to research on the relation of yield and grain quality. The yields of two heavy panicle weights indica-japonica hybrid cultivars were significantly higher than that of two medium panicle weight rice cultivars. The cooking and eating quality and starch properties of different panicle type cultivars were evaluated. Yongyou 6715 (medium panicle) and Yongyou 1852 (heavy panicle) got the relatively higher cooking and eating quality. Rice cultivars with medium panicle weight had more large starch granules and higher relative crystallinity than cultivars with heavy panicle weight. Transition temperature and retrogradation enthalpy (ΔHret) of medium panicle type cultivars were significantly higher than that of heavy panicle type cultivars. There was no significant difference in amylose content among different panicle type cultivars. Protein content of heavy panicle type cultivar was higher than that of medium panicle type cultivar, and protein content is the main factor affect cooking and eating quality in this study. The cultivar Yongyou 6715 got the highest taste value with the lowest protein content. Thus, it is suggested that the emphasis on improving rice cooking and eating quality of indica-japonica hybrid rice cultivars is how to reduce the protein content in rice grain. According to the results of this study, medium panicle type with high grain weight is the desired panicle type for high quality indica-japonica hybrid rice breeding.